Sleep patterns and long-term mortality among older Israeli adults: a population-based study - Lital Keinan-Boker; Yariv Gerber; Saar Ashri; Gali Cohen; Tal Hasin (BMJ Public Health)
Introduction The joint association of night-time sleep duration and daytime napping (siesta) with mortality remains elusive. We explored sleep patterns and long-term mortality in older adults and tested whether the relationship is modified by cognitive function.Methods We analysed data from 1519 participants in the National Health and Nutrition Survey of older adults aged 65+ years (‘Mabat Zahav’), conducted by the Israel Center for Disease Control during 2005–2006. A detailed questionnaire was administered at study entry to gather information on sleeping habits, including night-time sleep duration and siesta. A Mini-Mental State Examination was administered to assess cognitive status (score <27 considered impaired). Mortality data were obtained from the Ministry of Health (last follow-up: June 2019; 782 deaths). Cox models were constructed to estimate the HRs for mortality associated with sleep patterns, defined according to night sleep duration (>8 vs ≤8 hours) and siesta (Y/N). Spline regression models were constructed to examine the linearity of the association across cognitive statuses.Results Sleep categories among participants (mean age 75; 53% women) included 291 (19.2%) with long night sleep and siesta, 139 (9.1%) with long night sleep and no siesta, 806 (53.1%) with short night sleep and siesta, and 283 (18.6%) with short night sleep and no siesta. HRs for mortality were 2.07 (95% CI: 1.63 to 2.62), 1.63 (95% CI: 1.22 to 2.18) and 1.43 (95% CI: 1.16 to 1.76) in the former three versus latter sleep patterns, respectively. Multivariable adjustment for sociodemographic, behavioural and clinical covariates attenuated the HRs to 1.27–1.41 (all p<0.05). The relationship between night sleep duration and mortality was linear (plinearity=0.047) among cognitively preserved individuals and U-shaped (pnon-linearity<0.001) among cognitively impaired ones.Conclusions Prolonged night sleep and siesta were associated with increased mortality, a relationship that varied by cognitive performance.